"Overview" Perkembangan Investasi di Indonesia sebuah pengantar - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1994)
ABSTRACT icle describes briefly the development of invest ent in Indonesia since the Government released both foreign and dmestic investment laws in 1967 and 1968. Facing investment encouragem nt are some problems and constraints, such as poor infrastructure (especially in outer Java), complex government regulations, lack of financial support by the banking sector, poor capability of human resources to handle technological changes, high competition among host countries to attract foreign investment, and lack of support from the service sector. Traditionally, the secondary sector has been more interested in "quick yielding" investments as opposed to the primary sector which is supported by natural resources. Actually, this kind of investment has been backed-up by a potentially large domestic market. Most are concentrated in the textile, chemical, metal goods, food, plywood, paper and non-metal mineral industries. The author says that the government should pay more attention for continuing their existing deregulation policy to increase both the number and value of new investment. The policy will improve productivity and efficiency for a more condusive and competitive economy, as a part of the preparation for the era trading-blocks and a global market economy.